Nonoscillatory Solutions for Higher-Order Neutral Dynamic Equations on Time Scales. (1st August 2010) - Sun, Taixiang; Xi, Hongjian; Peng, Xiaofeng; Yu, Weiyong
Abstract : We study the higher-order neutral dynamic equation a ( t ) [ ( x ( t ) − p ( t ) x ( τ ( t ) ) ) Δ m ] α Δ + f ( t, x ( δ ( t ) ) ) = 0 fort ∈ [ t 0, ∞ ) 𝕋 and obtain some necessary and sufficient conditions for the existence of nonoscillatory bounded solutions for this equation.